2008
DOI: 10.1007/s10029-008-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

Pain, quality of life and recovery after laparoscopic ventral hernia repair

Abstract: LVHR was associated with considerable postoperative pain and fatigue in the first postoperative month, prolonging the time of convalescence and significantly affecting patients' quality of life up to 6 months postoperatively. Mesh fixation with fibrin glue or other non-invasive/degradable products seems promising for reducing pain and it should be investigated in future randomised trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 25 publications
7
73
0
6
Order By: Relevance
“…The three pain components deep abdominal pain (visceral), incisional pain (somatic) and shoulder pain (referred pain) have been differentiated after laparoscopic cholecystectomy [8,9], fundoplication [10] and laparoscopic ventral hernia repair [11]. In the present study, visceral pain dominated over incisional pain and shoulder pain, and this is comparable to findings after laparoscopic incisional hernia repair [11].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The three pain components deep abdominal pain (visceral), incisional pain (somatic) and shoulder pain (referred pain) have been differentiated after laparoscopic cholecystectomy [8,9], fundoplication [10] and laparoscopic ventral hernia repair [11]. In the present study, visceral pain dominated over incisional pain and shoulder pain, and this is comparable to findings after laparoscopic incisional hernia repair [11].…”
Section: Discussionsupporting
confidence: 75%
“…Previous pain studies in patients undergoing laparoscopic cholecystectomy [8,9], fundoplication [10] and incisional hernia repair [11] have shown different pain patterns with varying degrees of pain intensity, time course and different dominance of visceral, incisional and shoulder pain, arguing for a differentiated analgesic approach depending on the type of laparoscopic operation [7].…”
mentioning
confidence: 99%
“…The investigators noted a 9% recurrence rate in the patients whose mesh had been fixed by tacks alone, more than twice the rate seen with sutures plus tacks. Despite these advantages, use of aggressive methods of mesh fixation has been associated with chronic pain and discomfort in up to 20% of patients [2,3,20,21,23,24,36]. Leblanc's 2003 study reported a 4.5% immediate and 1% prolonged ([8 weeks) postoperative pain rate with LVHR [36].…”
Section: Discussionmentioning
confidence: 98%
“…Prior to integration, a repair may be compromised at the site of fixation, and thus published data have shown that transfascial suture with tacks demonstrated superior tensile strength, yielding the lowest recurrence rates [2,3,[14][15][16][17][18]. Despite this efficacy, transfascial repair is associated with up to a 21% rate of local pain and discomfort that may persist beyond 6 months postoperatively [2,3,7,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…Langbach et al [10] found that 60.5% of patients were satisfied even 10 years after laparoscopic ventral hernia repair, although a recurrence rate of 66.2% in that study could explain the relatively low satisfaction rates after longer periods of follow-up. Eriksen et al [11] reported that pain was associated with dissatisfaction after laparoscopic ventral hernia repair in the absence of recurrences, while Liang et al [12] reported 74.6% satisfaction following laparoscopic ventral hernia repair, with decreased patient satisfaction mainly associated with perception of poor cosmetic outcome and chronic pain.…”
Section: Discussionmentioning
confidence: 99%